2012
DOI: 10.1111/j.1365-4632.2011.05310.x
|View full text |Cite
|
Sign up to set email alerts
|

The risk of developing non‐melanoma skin cancer, lymphoma and melanoma in patients with psoriasis in Taiwan: a 10‐year, population‐based cohort study

Abstract: Psoriasis carries an elevated risk of NMSC and lymphoma. This effect is modified by the severity of psoriasis, age, gender, and geographic location.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 43 publications
1
28
0
Order By: Relevance
“…Several studies showed that the NHIRD database is appropriate for use in pharmacoepidemiologic research [12, 16, 17]. The NHIRD database contains participant demographics and detail claim history, which includes medications prescribed, medications quantity, route of administration, individual diagnoses, operations, and outpatient and inpatient electronic claim records.…”
Section: Methodsmentioning
confidence: 99%
“…Several studies showed that the NHIRD database is appropriate for use in pharmacoepidemiologic research [12, 16, 17]. The NHIRD database contains participant demographics and detail claim history, which includes medications prescribed, medications quantity, route of administration, individual diagnoses, operations, and outpatient and inpatient electronic claim records.…”
Section: Methodsmentioning
confidence: 99%
“…A cohort study of 7,061 Taiwanese psoriasis patients found that psoriasis patients were more likely to develop non-melanoma skin cancer and lymphoma 156. Patients who had never received systemic therapy were also more likely to develop non-melanoma skin cancer and lymphoma, suggesting that psoriasis could be an independent risk factor for these malignancies 156…”
Section: Cancermentioning
confidence: 99%
“…[15][16][17] In addition, either because of their disease or treatments they might have or had received, patients with psoriasis are at increased risk for certain other diseases such as cancers, including lymphoma and skin cancer, [18][19][20] and autoimmune diseases. 2,[21][22][23][24][25] As patient information may inform clinical care, dermatologists need to obtain, document, and act on key pieces of information about patients with psoriasis to provide optimal care.…”
mentioning
confidence: 99%